2022
DOI: 10.3389/fpls.2022.970535
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling on the analysis of different parts of Schisandra chinensis based on UPLC-QTOF-MS with comparative bioactivity assays

Abstract: The Schisandra chinensis is an important edible plant, and previous phytochemical research focused on the S. chinensis fruit (SF) due to its long history as traditional Chinese medicine. Schisandra chinensis fruit was used as an astringent tonic to astringe the lungs and the kidneys, replenish energy, promote the production of body fluids, tonify the kidney, and induce sedation. The components of S. chinensis, such as its stems (SS), leaves (SL), and roots (SR), have drawn little attention regarding their meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The S. chinensis fruit contains the highest amount of lignans, accounting for approximately 2% of its dry weight ( 44 ). A comparative study was conducted on the amount of lignan in S. chinensis extracts of fruit, leaves, stems, and roots using ultra performance liquid chromatography (UPLC)-Q-TOF-MS ( 45 ). The researchers found that the roots contained higher contents of gomisin D, schisandrol B, schisanterin C, kadsuranin, and kadlongilactone F than those in the fruits, and these components were closely related to their antioxidant and anti-inflammatory activities ( 45 ).…”
Section: Nutritional and Active Components Of Schisandra Ch...mentioning
confidence: 99%
See 1 more Smart Citation
“…The S. chinensis fruit contains the highest amount of lignans, accounting for approximately 2% of its dry weight ( 44 ). A comparative study was conducted on the amount of lignan in S. chinensis extracts of fruit, leaves, stems, and roots using ultra performance liquid chromatography (UPLC)-Q-TOF-MS ( 45 ). The researchers found that the roots contained higher contents of gomisin D, schisandrol B, schisanterin C, kadsuranin, and kadlongilactone F than those in the fruits, and these components were closely related to their antioxidant and anti-inflammatory activities ( 45 ).…”
Section: Nutritional and Active Components Of Schisandra Ch...mentioning
confidence: 99%
“…A comparative study was conducted on the amount of lignan in S. chinensis extracts of fruit, leaves, stems, and roots using ultra performance liquid chromatography (UPLC)-Q-TOF-MS ( 45 ). The researchers found that the roots contained higher contents of gomisin D, schisandrol B, schisanterin C, kadsuranin, and kadlongilactone F than those in the fruits, and these components were closely related to their antioxidant and anti-inflammatory activities ( 45 ). The antioxidant capacity of the main lignans in S. chinensis extract was determined by using the HPLC-online TEAC method.…”
Section: Nutritional and Active Components Of Schisandra Ch...mentioning
confidence: 99%
“…Increasing modern research shows Schisandra extracts may help protect liver cells from injury and inflammation, enhance detoxification capacity, improve tissue regeneration, and slow progression of fibrosis. These beneficial mechanisms make Schisandra chinensis a promising herbal medicine for further research on chronic liver therapies [15].…”
mentioning
confidence: 99%